FORMULATION AND EVALUATION OF PRONIOSOMAL GEL-BASED TRANSDERMAL DELIVERY OF ATORVASTATIN CALCIUM BY BOX–BEHNKEN DESIGN - SOUJANYA C; RAVI PRAKASH P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of this study was to investigate the combined influence of three independent variables in the preparation of atorvastatin proniosomes by coacervation-phase separation method. Methods: On the basis of the preliminary trials, a 3-factor, 3-level Box–Behnken design was employed to study the effect of cholesterol, soya lecithin, and Span 60 independent variable on dependent variables (particle size and % entrapment efficiency). Transmission electron microscopy analysis of optimized formulation has demonstrated the presence of individual proniosomes in spherical shape. Results: Atorvastatin optimized proniosomal formulation F2 shown better particle size and % entrapment efficiency, and also, the drug release was 99.72% within 24 h in slow and controlled manner when compared with control. Kinetic analysis of drug release profiles showed that the drug release was followed by zero-order manner with Korsmeyer–Peppas model, which implies super case II release kinetics. The particle size and zeta potential of the optimized atorvastatin proniosomal gel were found to be 65.72 and −10.5, respectively. The optimized batch of proniosomes was used for the preparation of atorvastatin-based proniosomal hydrogel by incorporating hydrated proniosomes to carbopol matrix to enhance the stability and viscosity of the system. Conclusion: The enhanced skin permeation, for a prolonged period of time, may lead to improved efficacy and better patient compliance. This study suggests that proniosomal gel-containing atorvastatin could perform therapeutically better effects than the conventional formulations.